Beleza, elegância e roupas, os homens nos espaços da cidade (Maringá na década de 1950) - Silva, Guilherme Telles da (2015)
Men, fashion and masculinities in cities. This is the approach proposed to study the photographs of the "pioneers men" of the city of Maringa, Parana, in the 1950s The empirical work involved a survey and analysis of pictures from the memory collections, available in Maringa Historical blog, and survey the period of the media outlets. The bibliographic nature of documents on the history of the city and fashion studies, in particular, the relationship of men with the clothes and material culture justifying the approaches of research products. In the approach, we determine the links between the costumes and the creation of images for the male and masculinities; show how social and economic distinctions are provided by the costumes; highlight the roles played by clothing in the production of meanings for power and prestige and the creation of visual cues to differentiate rich and poor. Revealed thus transits between the sartorial significance for their various appropriations and significance of networks, particularly as protection in relation to the harsh environment and the construction of images for daring courage and masculine strength. To this face, reveal the modernization of the city was set up by the presence of young men, their clothing and their lifestyles. The creation of sociability spaces is expressive of the changes in men and masculinities